Urgency and Impact of Green Taxes Implementation in Encouraging Green Business Post Covid-19 - Rahmi, Notika; Selvi, Selvi; Purwaningtias, Agitta Sofyan (Majalah Ilmiah Bijak, 2024)
This study aims to examine the urgency, impact and strategy of Green Taxes in encouraging Green Business after the Covid-19 pandemic. This study uses a qualitative approach with a comparative descriptive type of research, in which the application of Green Taxes in various countries for the purpose of encouraging Green Business is compared to the conditions in Indonesia. The results of the research show that environmental damage due to industrial activities that occur in Indonesia can harm the country because, coupled with the COVID-19 pandemic, the end of which is not yet known, it will increase the state’s health spending. It. Many countries have successfully implemented Green Taxes and changed their business patterns to be environmentally friendly, although the negative impact of the green tax implementation, i.e. a decrease in net profit in the business sector, can result in layoffs and a decrease in tax revenue in several sectors. The application of Green Taxes in Indonesia is still at the level of the domestic tax function, which can be seen in the increasing target and realization of Green Taxes each year. The government must be more assertive in enforcing Green Taxes and be transparent in the use of the funds. Supervision in the implementation of the green tax policies must also be improved so that the expected goals can be achieved.